RESTORASI SISTEM PENDIDIKAN KARAKTER BERBASIS AL-QUR'AN DI SMAIT NURUL FAJRI SEBAGAI AKTUALISASI KEMAJUAN PERADABAN - Shalahuddin, Muhammad; Syaf, Solehudin; Hambali, Adang; Basri, Hasan (Universitas Pendidikan Indonesia, 2024)
Abstracts This research aims to explore the implementation of restoring character education system based on Al-Qur'an in SMAIT Nurul Fajri as an effort to actualize the advancement of civilization. SMAIT Nurul Fajri emerges by providing a strong foundation of Islamic teachings in realizing a civil society in the